Prenatal Screening for Chromosomal Defects - Veronika Frisova (Reproductive Medicine)
Chromosomal defects are a significant cause of perinatal death and childhood disability, occurring in 3.6–6.0 per 1000 births in unscreened populations. Common chromosomal defects include trisomy 21, 18, and 13, triploidy, and sex chromosome abnormalities. Screening for these defects began in the mid-1960s with the advent of amniocentesis, and various methods have since been developed to improve screening performance. Initial screening was based solely on maternal and gestational age, a method incorporated later into all subsequent screening methods giving an a priori background risk. This a priori background risk, which is further refined by maternal serum biochemistry, results of ultrasound examinations, and most recently, results of non-invasive prenatal testing by cell-free DNA in maternal blood. This paper will describe methods of screening for all chromosomal defects and their performance. Unlike most reviews, this paper covers not only screening tests for Down syndrome, but also screening methods for the other most common and less common chromosomal defects.